Persistence and distribution of dinotefuran in tree of heaven - Keyzer, Justin; Lewis, Phillip; McCullough, Deborah G. (Frontiers in Insect Science, 2023)
Spotted lanternfly (SLF) (Lycorma delicatula (White)), an invasive planthopper discovered in Pennsylvania, U.S.A. in 2014, feeds for approximately six months by sucking phloem sap from trunks and limbs of tree of heaven, Ailanthus altissima, along with several native trees and woody vines. Basal trunk sprays of dinotefuran, a systemic neonicotinoid insecticide, are commonly used to reduce SLF densities and spread. Information on dinotefuran persistence and within-tree distribution can help identify optimal timing of annual basal trunk sprays, facilitating efficient use of available resources. We applied dinotefuran to 20 uninfested A. altissima trees in early April then periodically sampled foliage to monitor insecticide residues. Foliar dinotefuran residues averaged (± SE) 7.8 ± 1.1 and 6.3 ± 1.2 in July and August, respectively, then dropped significantly to 2.6 ± 0.5 ppm in September. In a second study, 20 A. altissima trees were similarly treated with dinotefuran basal trunk sprays in early June. Trees were felled to collect foliage and phloem from branches and the trunk in either mid-July or September. Foliar residues averaged 12.7 ± 1.3 and 14.6 ± 2.2 ppm in July and September, respectively. For trees felled in July, residues were detected in phloem collected from below the spray line on trunks of seven trees and above the spray line on three trees, averaging 8.6 ± 4.4 and 7.4 ± 2.9 ppm, respectively. In trees felled in September, phloem from below spray lines of seven trees averaged 3.7 ± 1.3 ppm but dinotefuran was not detected in phloem from above the spray line on any trees. Dinotefuran was not detected in phloem sampled from any branches in either July or September. Results suggest dinotefuran basal trunk sprays applied between late May and mid June should persist long enough to effectively control SLF late instars and adults.